Upaya Meningkatkan Kemampuan Berhitung melalui Penggunaan Media Ular Tangga Matematika pada Peserta Didik Kelas 2 SD Negeri Glagahombo 1 - Aninda Budi Pawestri; Ari Wibowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve arithmetic skills through the use of a Snakes and Ladders Mathematics board game as a learning medium. The research was motivated by the low numeracy performance of second-grade students at SD Negeri Glagahombo 1. The teacher plays a crucial role in designing innovative and enjoyable learning strategies that encourage students to engage actively. Before the intervention, the learning success rate was only 50% with an average score of 69,92, which was below the minimum mastery criterion of 75. To address this issue, the researcher and teacher collaborated to implement the